Longitudinal Effects of Distress and Its Management During COVID-19 Lockdown in Spain - Flor-Arasil, Patricia; Rosel, Jesús F.; Ferrer, Emilio; Barrós-Loscertales, Alfonso; Machancoses, Francisco H. (Frontiers in Psychology, 2021)
The COVID-19 pandemic that hit Spain from March 2020 forced the strict confinement of the population for two months. The objectives of this study were (a) to assess the magnitude and duration of the influence of confinement on people's Distress; (b) to study the temporal sequence of stress; and (c) to show how different day-to-day activities and personal variables influence perceived Distress levels. Method A daily registration was completed by 123 people, ages ranged from 21 and 75 years old (X ̅ = 43, SD = 10 years), 40 men (32%) and 83 females (68%). During the 45 days of forced-lockdown, from March 19th to May 3rd, participants were asked to respond a socio-demographic survey and a daily record comprised by the MASQ-D30 and some day-to-day behaviours. Pooled Time Series was applied to establish what effect time had on the dependent variable. Results Distress was significant (F = 16.270; df: 1,485; p < .001) and the trend of the series was well represented. Distress increased at the beginning of the lockdown compared to the end, declining in the days after showing a 'hillside' shape tending to stabilize. The Distress has a 14-day autoregressive function where gender, the physical activity, sexual activity, listening to music or teleworking also influence Distress. It has been hypothesized that the intercept presents variability at level 2 (individual), but it has not been significant. Interactions between gender - Telecommuting, and Gender - Physical Activity were observed. Approximately 66% of the variance of Distress was explained (R2 = .663). Discussion At the beginning of the lockdown, average levels of Distress were well above the levels of the end (z = 3.301). The individuals in the sample have followed a similar process in the development of Distress. During the lockdown, the "memory" of Distress has been 2 weeks. Our results indicate that levels of Distress depend on the activities did during lockdown. Interaction exists between gender and some behavioural variables that barely influence Distress in male but decreases in female. The importance of routine maintenance and gender differences must be considered to propose future interventions during confinements.